Implementasi UU No 23 Tahun 1997 Tentang Pencemaran Lingkungan Hidup: Studi Terhadap Masyarakat Kabupaten Gresik - Siti Awaliyah (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2006)
This study aims to analyze the implementation of Law No. 23 of 1997 concerning Environmental Management in Gresik Regency, especially in handling cases of environmental pollution. Gresik Regency, as an industrial area, faces major challenges in maintaining a balance between economic development and environmental sustainability. This study uses a qualitative method with a field and literature study approach, involving regulatory analysis, interviews with stakeholders, and observation of the impact of pollution. The results showed that the implementation of Law No. 23 of 1997 still faces various obstacles, such as weak supervision, lack of public awareness, and dominant industrial interests. Although there are efforts to enforce environmental law and policy, their effectiveness still needs to be improved. This study emphasizes the importance of synergy between the government, industry, and the community in implementing environmental regulations more optimally.